Biodegradable polymers and composites - process engineering to commercialization - Binod, Parameswaran; Raveendran, Sindhu; Pandey, Ashok (Amsterdam, Netherlands : Elsevier, 2021)
'Biodegradable Polymers and Composites - Process Engineering to Commercialization is designed in such a way that it not only gives basic knowledge but also contains information regarding conventional and advanced technologies, socio-economic aspects, techno-economic feasibility, modelling tools and detailed Life Cycle Analysis in biopolymer production. The book discusses the advantages and importance of biopolymers over the conventionally produced plastics. Biodegradable Polymers and Composites highlights: the conventional and advanced strategies for biopolymer production; information regarding process engineering and commercialization of biopolymers; models and available modelling techniques in the sector of biopolymer production; and global case studies, opportunities and challenges (technical constraints, institutional constraints and social constraints) associated with biopolymer production'--
Includes bibliographical references and index.
Keywords: Biopolymers; Polymers -- Biodegradation; Polymers -- Biotechnology